Evolutionary consequences of self-fertilization in plants - Wright, Stephen I.; Kalisz, Susan; Slotte, Tanja (Proceedings of the Royal Society. B, Biological sciences, 2013)
The transition from outcrossing to self-fertilization is one of the most common evolutionary changes in plants, yet only about 10–15% of flowering plants are predominantly selfing. To explain this phenomenon, Stebbins proposed that selfing may be an ‘evolutionary dead end’. According to this hypothesis, transitions from outcrossing to selfing are irreversible, and selfing lineages suffer from an increased risk of extinction owing to a reduced potential for adaptation. Thus, although selfing can be advantageous in the short term, selfing lineages may be mostly short-lived owing to higher extinction rates. Here, we review recent results relevant to the ‘dead-end hypothesis’ of selfing and the maintenance of outcrossing over longer evolutionary time periods. In particular, we highlight recent results regarding diversification rates in self-incompatible and self-compatible taxa, and review evidence regarding the accumulation of deleterious mutations in selfing lineages. We conclude that while some aspects of the hypothesis of selfing as a dead end are supported by theory and empirical results, the evolutionary and ecological mechanisms remain unclear. We highlight the need for more studies on the effects of quantitative changes in outcrossing rates and on the potential for adaptation, particularly in selfing plants. In addition, there is growing evidence that transitions to selfing may themselves be drivers of speciation, and future studies of diversification and speciation should investigate this further.